KONSEP TARBIYAH DAN RELEVANSINYA DENGAN NILAI-NILAI SISTEM PENDIDIKAN ISLAM MODERN (ANALISIS TERMINOLOGIS DAN FILOSOFIS ) - Lina Afriani (Yayasan An-Nur Meunara Baro, 2025)
In terms of terminology, tarbiyah is defined as the process of guiding and developing the potential of students (physical, intellectual, and spiritual) gradually towards perfection (insan kamil), and in line with divine values. Meanwhile, in terms of philosophy, tarbiyah focuses on the role of humans as Khalifah on earth and their responsibility as bearers of Amanah. The ultimate goal is to produce individuals who are devoted (ubudiyyah) to Allah SWT and function as Rahmatan lil 'alamin. Classical scholars (Al-Ghazali) view it as purification of the soul (tazkiyatun nafs), while contemporary scholars emphasize the balanced development of intellectual, moral, social, and spiritual potential (al-wasathiyyah). This study argues that the values of tarbiyah ruhiyah, Aqliyah, Khuluqiyah, and Ijtima'iyyah are still very relevant in the modern education system because they are able to respond to the challenges of globalization and the moral crisis. Tarbiyah also encourages education that focuses on character (cognitive, affective, psychomotor), is comprehensive, and positions teachers as murabbi with the ultimate goal of forming a complete Insan Kamil. This study uses a qualitative approach with a library research design and a Systematic Literature Review (SLR) method. The results of this study show the relevance between the concept of tarbiyah and Modern Islamic Education.